Adoption of Climate-Smart Agriculture: Colombia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
As part of ongoing research in East and West Africa and Latin America, CCAFS spent time in the field in Colombia to determine the challenges that could prevent farmers from adopting climate-smart agricultural techniques. August 2013. Photos: C Peterson (CIAT-CCAFS)